Ground motion simulation for the 21 May 2021 Ms 6.4 Yangbi, China, earthquake using stochastic finite-fault method. Issue 1 (February 2023) - Wang, Tianjia; Shen, Yonggang; Xie, Xu; Weng, Weipeng
On 21 May 2021, a 6.4-magnitude earthquake occurred in Yangbi County, Yunnan Province, China. To reproduce the ground motion characteristics of this earthquake, the stochastic finite-fault method was adopted. The ground motion records were analyzed to determine the source, path, and site parameters. Based on the optimization algorithm, the stress drop was set to 10 bar. The S-wave attenuation relation ( QS = 122.7 f 0.44 ) was calculated by the spectral decay method. For the site effect, the site amplification was corrected using the horizontal-to-vertical spectral ratio method, and the zero-distance kappa filter had a value of 0.0328 s. To verify the reliability of the input parameters, the simulated 5%-damped pseudo-spectral acceleration, time history, and Chinese instrumental intensity were compared with those observed at six stations and finding acceptable consistency. Furthermore, the fitted model was used to simulate the ground motion of 2279 nodal points in the area, and the seismic intensity contours were obtained. Finally, the earthquake damage assessment was performed in the Yangbi County, and the difference between the designed spectral acceleration and that simulated at a specific period was regarded as the degree of earthquake damage. It was found that the reinforced concrete structures near the epicenter have sufficient safety reserves, and the earthquake damage was not serious. In summary, the stochastic finite-fault method with calibrated parameters could effectively synthesize the ground motion of specific sites, thus providing a basis for the earthquake damage assessment of engineering buildings.